La dimensión política de lo irreal: el componente ideológico en la narrativa fantástica española y catalana - Gregori, Alfons (Wydawnictwo Naukowe UAM, 2015)
The central issue of this book is to analyse fantastic short stories published from the late 19th century up until the 21th century by authors writing in Spanish and Catalan. The author studies the role that ideological elements play so that they increase the possible meanings of fantastic literature. Special attention is given to some themes discernible in the texts, such as the figure of the double, objects with preternatural powers and other fantastic phenomena. The book starts through a critical presentation of different theories on the literary fantastic, which here is understood as an independent narrative mode. Later it goes on considering the most important theories about the concept of ideology for the progression of this work, that is, with regard to categories related to the discourse of fantasticity and some historical aspects. These concepts and theories are applied to analyse a selection of literary works by renowned authors in fantastic fiction from the Iberian Peninsula: Emilia Pardo Bazán, Miguel de Unamuno, Miguel Sawa, Pío Baroja, Luis Valera, Noel Clarasó, Álvaro Cunqueiro, Juan José Millás, José María Merino, Cristina Fernández Cubas, and José María García Hernández, all writing in Spanish, as well as Joaquim Ruyra, Diego Ruiz, Pere Calders, Joan Perucho, Maria Aurèlia Capmany, Maria Antònia Oliver, Jaume Fuster, and Albert Sánchez Piñol writing in Catalan.

Książka poświęcona jest analizie opowiadań fantastycznych opublikowanych od końca XIX wieku aż po wiek XXI przez pisarzy tworzących w językach hiszpańskim i katalońskim. przez pisarzy tworzących w językach hiszpańskim i katalońskim. Autor omawia rolę, jaką pełnią w nich elementy ideologiczne mające wpływ na wieloznaczność narracji. Szczególną uwagę poświęca pojawiającym się w tekstach motywom, takim jak: postać sobowtóra, przedmioty o nieprawdopodobnych właściwościach oraz inne zjawiska fantastyczne. Analizę tę poprzedza szczegółowy, wnikliwy przegląd wypracowanych przez krytykę teoretycznych stanowisk dotyczących różnorodnych koncepcji pojęcia ideologii i literatury fantastycznej. Zostały one omówione w odniesieniu do kategorii związanych z dyskursem fantastyczności oraz niektórych aspektów historycznych, a następnie posłużyły do omówienia wybranych tekstów uznanych twórców literatury fantastycznej z obszaru Półwyspu Iberyjskiego.
The Political Dimension of the Unreal: Ideology in Spanish and Catalan Fantastic Narrative
Keywords: literatura fantastyczna; opowiadania katalońskie; opowiadania hiszpańskie; ideologia; literatura i polityka